Case reportsDelayed presentation of traumatic left hemidiaphragm rupture in a child - Matuszczak, Ewa; Dębek, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
The authors present the case report of a 6-year-old girl admitted to the ICU after being knocked over by a car. The girl had an extensive wound of the hypogastric area - a soft tissue injury that required surgery. Ultrasound (US) of the abdominal cavity, CT of the head, and X-ray examination of the chest, spine, and abdomen did not reveal any signs of internal organ injuries or bone fractures. The wound was closed in layers. Control CT of the head, US of the abdomen, and X-ray of the chest were normal. On the 6th day, the patient’s general condition deteriorated. Chest X-ray with a nasogastric tube showed a loss of the left diaphragmatic outline and a large gastric shadow occupying the left hemithorax and displacing the mediastinum to the right. A left-sided traumatic diaphragmatic rupture with gastrothorax was diagnosed. The patient was immediately operated on. The girl made an uneventful postoperative recovery. Conclusions: Careful interpretation of the chest radiograph and early surgical intervention are likely to yield good outcomes in patients with posttraumatic diaphragmatic rupture and diaphragmatic hernia. All patients with possible diaphragm damage and recurrence of pulmonary dysfunction or intestinal symptoms (such as obstruction, nausea, and pain) should be investigated for posttraumatic diaphragmatic hernia.